PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DIMEDIASI EMPLOYEE ENGAGEMENT PADA KANTOR DIREKTORAT JENDERAL BEA DAN CUKAI SULAWESI BAGIAN SELATAN - Akhmad Muhammadin (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2025)
This study aims to examine and analyze the influence of Work Discipline and Compensation on Employee Performance, Mediated by Employee Engagement at the Directorate General of Customs and Excise (DJBC) Office in South Sulawesi. Data collection used primary data using a questionnaire technique, with samples obtained from employees of the Directorate General of Customs and Excise (DJBC) Office, with a saturated sample size of 91 employees. The questionnaire results were tested using SPSS Version 26 software with instrument testing, classical assumptions, and path analysis Based on the analysis, this study proves that there are two hypotheses: the first hypothesis is that Work Discipline has a positive and significant effect on Employee Engagement. Second, compensation has a positive and significant effect on the Directorate General of Customs and Excise (DJBC). Third, employee engagement has a positive and significant effect on employee performance. Fourth, work discipline has a positive and significant effect on employee performance. Fifth, compensation has a positive and significant effect on employee performance. Sixth, work discipline has no significant effect on employee performance through employee engagement. Seventh, compensation has no significant effect on employee performance through employee engagement.Keywords: Work Discipline, Compensation, Employee Engagement, Employee Engagement